A Propensity to Protect : Butter, Margarine and the Rise of Urban Culture in Canada - Heick, W. H. (Book collections on Project MUSE., 2006)
For Canada the last century was one of great social and economic change: an increasingly urban population witnessed shifts from an agricultural to a mixed economy and from moderate to greater wealth. Heick chronicles how changing attitudes toward butter and margarine reflected the nature of that society. He demonstrates how the ban on the manufacture, importation, and sale of margarine was instigated in 1986 at the behest of the nascent, yet influential diary industry, particularly in Ontario. This ban was based on the premise that margarine was not a pure food. Despite the lifting of the ba.